Sodium butyrate protects against lipopolysaccharide-induced liver injury partially via the GPR43/ β-arrestin-2/NF-κB network. (22nd November 2020) - Luo, Qian-Jiang; Sun, Mei-Xing; Guo, Yun-Wei; Tan, Si-Wei; Wu, Xiao-Ying; Abassa, Kodjo-Kunale; Lin, Li; Liu, Hui-Ling; Jiang, Jie; Wei, Xiu-Qing
Abstract: Background: Butyrate acts as a regulator in multiple inflammatory organ injuries. However, the role of butyrate in acute liver injury has not yet been fully explored. In the present study, we aimed to investigate the association between butyrate and lipopolysaccharide (LPS)-induced acute liver injury and the signaling pathways involved. Methods: LPS-induced acute liver injury was induced by intraperitoneal injection of LPS (5 mg/kg) in G-protein-coupled receptor 43 (GPR43)-knockout (KO) and wild-type female C57BL/6 mice. Sodium butyrate (500mg/kg) was administered intraperitoneally 30 min prior to LPS exposure. Liver injury was detected by serum markers, tissue morphology, and terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL). Pro-inflammatory-factor levels were detected by enzyme-linked immunosorbent assay and real-time polymerase chain reaction (RT-PCR). Cell models were first treated with sodium butyrate (4 μmol/mL), followed by LPS (1 μg/mL) half an hour later in GPR43 small interfering RNA (siRNA)-transfected or control RAW264.7 cells. Cell-inflammation status was evaluated through detecting pro-inflammatory-factor expression by RT-PCR and also through checking toll-like receptor 4/nuclear factor-κB (TLR4/NF-κB)-element levels including TLR4, TRAF6, IKKβ, IкBα, phospho-IкBα, p65, and phospho-p65 by Western blot. The interaction between GPR43 and β-arrestin-2 was tested by co-immunoprecipitation. Results: Sodium butyrate reversed the LPS-induced tissue-morphology changes and high levels of serum alanine aminotransferase, aspartate transaminase, myeloperoxidase, TUNEL, and pro-inflammatory cytokines such as tumor necrosis factor-α and interleukin-6. The ameliorating effect of sodium butyrate was weakened in GPR43-KO mice and GPR43 siRNA RAW264.7 cells, compared with those of GPR43-positive controls. Sodium butyrate downregulated some elements of the TLR4/NF-κB pathway, including phospho-IκBα and phospho-p65, in RAW264.7 cells. Increased interactions between GPR43 and β-arrestin-2, and between β-arrestin-2 and IкBα were observed. Conclusion: Sodium butyrate significantly attenuated LPS-induced liver injury by reducing the inflammatory response partially via the GPR43/β-arrestin-2/NF-κB signaling pathway.